Synergistic Effect of Honey and Propolis on Cutaneous Wound Healing in Rats - Nasrin Takzaree; Abbas Hadjiakhondi; Gholamreza Hassanzadeh; Mohammad Reza Rouini; Azadeh Manayi (Acta Medica Iranica, 2016)
Accelerating wound healing is now considered as a principle clinical treatment and increasing the quality and speed of healing which has always been emphasized by the scientists. Propolis and honey are natural bee products with wide range of biological and medicinal properties. This study was aimed to determine the synergistic effect of honey and propolis in wound healing of rat skin. A total of 75 Wistar rats weighing 200-250 gr were placed under general anesthesia and sterile conditions. Then a square shape wound with 1.5*1.5 mm dimension was made on the back of the neck. Animals were randomly divided into control, honey, propolis, combined honey propolis and phenytoin 1% groups, respectively. Rats were randomly divided into the following groups: 4th, 7th and, 14th days of treatment in each period of study. Wound area in the experimental group was covered once daily with a fixed amount of thyme honey, propolis, propolis and honey and phenytoin cream (1%), the control group did not receive any treatment. For histological studies, during the fourth, seventh and fourteenth day’s rats were sacrificed and samples were taken from the wound and adjacent skin. After histological staining fibroblast, neutrophils, macrophages and vascular sections were counted in the wound bed. The macroscopic and microscopic evaluations showed that the percentage of wound healing on different days in the experimental and control groups were significant (P<0.05). The macroscopic and microscopic evaluation showed that the percentage of wound healing on different days in combined propolis and honey experimental group was significantly different from the control group (Multivariate ANOVA test) (P<0.05). Combined application of propolis and honey on the open wound healing in rats has a synergistic effect.